Environmental Influences as Causes and Curative Effects for Major Depressive Disorder - Karimatunnisa, Fatin (UM Purwokerto Press, 2025)
Major depressive disorder is one of the most common types of depression. This condition is characterized by feelings of depression, anhedonia, changes in cognitive function, changes in sleep, appetite changes, and guilt that lasts for two weeks and is characterized by loss of interest in or enjoyment of usual activities. Sufferers are usually aged 40 years and above, but nowadays, sufferers include teenagers and children. This study used a qualitative method by conducting interviews, listening to the viewpoints, and describing people with major depressive disorder as a data collection technique through reviews journals from PubMed and video interviews of survivors of this disease on social media platforms, which are then summarized from various background stories of survivors This depression contains bothersome things such as difficulty concentrating and sadness for an extended period. The causes vary from genetic to environmental factors. This article examines how the environment influences the causes and also the curative factors in major depressive patients.